Synthesis, characterization and metal ion sensing properties of novel pyridone derivatives phthalocyanines - (:unkn) unknown (WORLD SCI PUBL CO INC, 2016)
The design of novel substituted phthalocyanines closely follows the requirement of their planned applications. In this study, synthesize of novel pyridone derivatives metal-free and symmetrical cobalt(II) phthalocyanines was carried out to improve brightness. For this purpose; starting with 4-nitrophthalonitrile and 4-hydroxy-6-methyl-3-nitro-2-pyridone, 4-(6-methyl-3-nitro-2-oxo1,2- dihydropyridin-4-yloxy) phthalonitrile was prepared. Then 2(3), 9(10), 16(17), 23(24)-tetrakis[6-methyl- 3-nitro-2-oxo-1,2-dihydropyridin-4-yloxy] metal-free phthalocyaninato and 2(3), 9(10), 16(17), 23(24)-tetrakis[6-methyl-3-nitro-2-oxo-1,2-dihydropyridin-4-yloxy] phthalocyaninato Co(II) were synthesized by using 4-(6-methyl-3-nitro-2-oxo-1,2-dihydropyridin-4-yloxy) phthalonitrile, lithium metal and cobalt(II) acetate tetrahydrate in amyl alcohol, respectively. The sensing behavior of the film of derivatives metal-free and symmetrical cobalt(II) phthalocyanines for the online detection of heavy metal ions in water samples was investigated by utilizing an AT-cut quartz crystal resonator. It was observed that the adsorption of the analytes on the coating surface cause a reversible negative frequency shift of the resonator. Quartz crystal microbalance (QCM) functionalized with phthalocyanine, derivatives metal-free and symmetrical cobalt(II) phthalocyanines, are demonstrated to be sensors for the detection of heavy metal ions like Cd2+, Zn2+, Cu2+, Cr2+ and Co2+. Thus, QCM based sensor arrays are considered a promising platform for the direct analysis of aqueous samples.
Keywords: phthalocyanine; pyridone; cobalt; metal-free; heavy metal; detection; sensitivity; SANDWICH DILUTETIUM TETRAPHTHALOCYANINE; COBALT PHTHALOCYANINE; FILMS; REDUCTION